Dual Management of Electrons and Photons to Get High‐Performance Light Emitting Devices Based on Si Nanowires and Si Quantum Dots with Al2O3‐Ag Hybrid Nanostructures. (17th October 2018) - Ji, Yang; Lin, Zewen; Liu, Xiaolong; Liu, Jian; Yang, Huafeng; Li, Dongke; Liu, Jingjing; Xu, Jun; Li, Wei; Chen, Kunji
Abstract: Silicon quantum dot (Si QD)‐based light emitting devices are fabricated on Si nanowire (Si NW) arrays. Through inserting Al2 O3 ‐Ag hybrid nanostructures (Al2 O3 ‐Ag HNs) between Si NWs and Si QDs, both photoluminescence (PL) and electroluminescence (EL) are remarkably enhanced compared to the control sample. The PL enhancement can be mainly attributed to passivation effect of Al2 O3 to p‐type Si NWs and enlarged absorption cross‐section due to the local surface plasmon resonance effect of Ag nanoparticles. The EL intensity is enhanced by 14.9‐fold at the same injection current under a lower applied voltage, which may result from the high injection efficiency of electrons and the promoted waveguide effect of nanowire structures with Al2 O3 ‐Ag HNs. It is demonstrated that light emitting device performances can be well improved by careful management of both electrons and photons via controlling the interface conditions of Si NWs/Si QDs. Abstract : Silicon quantum dot based light emitting devices are fabricated on silicon nanowires. Through inserting Al2 O3 ‐Ag hybrid nanostructures, both photoluminescence and electroluminescence are obviously improved with the careful interface treatment. Dual management of electrons and photons is achieved simultaneously in the nanowire devices, which benefits the development of silicon based light emitting.